No Man’s Land or Neutral Ground: Perceived Gendered Differences in Ideologies of War - Marianne Moen (Norsk arkeologisk selskap, 2021)
This article approaches gender in the Viking Age as a fluid social category, to be understood through an intersectional lens alongside other cultural variables. Using material from the Vestfold region, the article argues that the perceived genders encountered in mortuary remains from the area display a significant amount of social similarities. It therefore proposes to explore the expression of social roles across, rather than within gendered lines. The approach challenges the traditional tendency of dividing gendered archaeological remains based on a few, select categories singled out from the grave goods. It suggests that a more open approach would avoid overlooking real and tangible levels of shared expressions between graves assigned different gender in many mortuary contexts.